Dynamic mechanical characterization of boron nitride nanotube—epoxy nanocomposites. Issue 6 (2nd November 2018) - Rahmat, Meysam; Naftel, Alex; Ashrafi, Behnam; Jakubinek, Michael B.; Martinez‐Rubi, Yadienka; Simard, Benoit
Abstract : Quasi‐static and dynamic performances of an epoxy adhesive with and without Boron nitride nanotubes (BNNTs) are studied here. This article investigates the thin film shear and bulk tensile properties of EPON 828/Epikure 3223. In addition to the neat epoxy material, specimens with 1 and 2 wt% concentrations of BNNTs were also tested. Double‐lap shear tests were performed at strain rates ranging from 4.0 × 10 −4 to 3.7 × 10 3 s −1 and it was found that neither the incorporation of BNNTs nor increasing the strain rate had a substantial effect on the shear properties of the thin adhesive layer. However, bulk tensile properties were seen to be sensitive to changes in strain rate. An increase in the strain rate from 5.5 × 10 −4 to 1.2 × 10 2 s −1 increased the tensile strength and Young's modulus by 39 and 113%, respectively; while the failure strain decreased by 49%. Additionally, the BNNT‐modified tensile specimens demonstrated up to 7% increase in tensile strength, up to a 16% increase in modulus, and a 9% decrease in the strain at failure. These results along with electron micrographs showed that due to pull‐out and bridging mechanisms of the nano‐reinforcements, the BNNTs are more effective in normal stress dominant applications, as opposed to shear stress. POLYM. COMPOS., 40:2119–2131, 2019. © 2018 Society of Plastics Engineers